Performance enhancement in AGC of multi-area power system with WOA optimized fo-2dof controller and facts controllers - Chandra Sahu, Prakash; Chandra Prusty, Ramesh (International Journal of Engineering and Technology, 2018)
This research article aims to develop Load Frequency Control (LFC) of equal three area with individual area comprises single thermal sys-tem and wind system and appropriated 3% of Generation rate constraint (GRC) is considered for thermal system to make non-linearity to overall system. For automatic generation control (AGC) the proposed secondary controller is a two degree of freedom (DOF) based frac-tional order Proportional, Integral, Derivative (PID) controller and used to reduce error for this study. For optimizing the gains of this pro-posed controller in a suitable manner a newly deterministic algorithm called Whale Optimization algorithm (WOA) is applied. Comparative performance analysis of different controllers like FO-2DOF-PID, 2DOF-PID, and PID is done in respect of settling time and peak over-shoot. Apart from this to improve quality of different dynamic responses some FACTS devices like Interlined power flow controller(IPFC), Static synchronous series compensator (SSSC) and Thyristor controlled series capacitor (TCSC) are implemented with FO-2DOF-PID controller and for superiority analysis a comparison is made between above optimized controllers.Â Â